Defining Breast Cancer Intrinsic Subtypes by Quantitative Receptor Expression. (23rd April 2015) - Cheang, Maggie C.U.; Martin, Miguel; Nielsen, Torsten O.; Prat, Aleix; Voduc, David; Rodriguez‐Lescure, Alvaro; Ruiz, Amparo; Chia, Stephen; Shepherd, Lois; Ruiz‐Borrego, Manuel; Calvo, Lourdes; Alba, Emilio; et al.
Abstract : Purpose: To determine intrinsic breast cancer subtypes represented within categories defined by quantitative hormone receptor (HR) and HER2 expression. Methods: We merged 1, 557 cases from three randomized phase III trials into a single data set. These breast tumors were centrally reviewed in each trial for quantitative ER, PR, and HER2 expression by immunohistochemistry (IHC) stain and by reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR), with intrinsic subtyping by research‐based PAM50 RT‐qPCR assay. Results: Among 283 HER2‐negative tumors with <1% HR expression by IHC, 207 (73%) were basal‐like; other subtypes, particularly HER2‐enriched (48, 17%), were present. Among the 1, 298 HER2‐negative tumors, borderline HR (1%–9% staining) was uncommon ( n = 39), and these tumors were heterogeneous: 17 (44%) luminal A/B, 12 (31%) HER2‐enriched, and only 7 (18%) basal‐like. Including them in the definition of triple‐negative breast cancer significantly diminished enrichment for basal‐like cancer ( p < .05). Among 106 HER2‐positive tumors with <1% HR expression by IHC, the HER2‐enriched subtype was the most frequent (87, 82%), whereas among 127 HER2‐positive tumors with strong HR (>10%) expression, only 69 (54%) were HER2‐enriched and 55 (43%) were luminal (39 luminal B, 16 luminal A). Quantitative HR expression by RT‐qPCR gave similar results. Regardless of methodology, basal‐like cases seldom expressed ER/ ESR1 or PR/ PGR and were associated with the lowest expression level of HER2/ ERBB2 relative to other subtypes. Conclusion: Significant discordance remains between clinical assay‐defined subsets and intrinsic subtype. For identifying basal‐like breast cancer, the optimal HR IHC cut point was <1%, matching the American Society of Clinical Oncology and College of American Pathologists guidelines. Tumors with borderline HR staining are molecularly diverse and may require additional assays to clarify underlying biology. Abstract : This study compared centrally performed clinical assays of quantitative ER, PR, and HER2 expression with molecular intrinsic subtypes identified by an open‐source, centroid‐based, subtype predictor in tumors collected across three phase III randomized clinical trials and determined the molecular populations within strongly hormone receptor‐positive tumors, borderline tumors, and triple‐negative tumors. Abstract : 摘要 目的 . 在由定量检测激素受体（HR）和HER2表达定义分类的范畴中，确定乳腺癌的原生亚型。 方法 . 我们将3项III期随机临床试验中的1 557个病例合并为一个数据集。对各乳腺癌试验中采用免疫组化（IHC）染色和逆转录定量聚合酶链反应（RT‐qPCR）检测的定量ER、PR和HER2表达，以及基于研究的PAM50RT‐qPCR方法进行原生亚型分型进行集中审核。 结果 . 283例IHC检测HR表达< 1%的HER2阴性肿瘤中，207例（73%）为基底细胞样型，还存在其他亚型，尤其是HER2高表达型（48例，17%）。在1 298例HER2阴性肿瘤中，HR临界表达水平（1% ∼ 9%染色）较少见（n = 39），并且这些肿瘤具有异质性：17例（44%）为管腔 A/B型，12例（31%）为HER2高表达型，仅7例（18%）为基底细胞样型。将这些病例纳入三阴乳腺癌的定义明显削减了基底细胞样癌患者数量（ P < 0.05）。在106例IHC检测HR表达< 1%的HER2阳性肿瘤中，HER2高表达亚型最常见（87例，82%），而在127例HR高水平表达（> 10%）的HER2阳性肿瘤中，仅69例（54%）为HER2高表达型，55例（43%）为管腔型（39例为管腔 B型，6例为管腔 A型）。RT‐qPCR法定量检测的HR表达得到了相似的结果。无论采用何种方法，基底样细胞病例很少表达ER/ ESR1 或PR/ PGR ，并且与HER2/ ERBB2 表达水平低于其他亚型相关。 结论 . 临床检验方法定义的患者亚组与原生亚型之间仍存在明显的不一致。鉴别基底细胞样乳腺癌的最佳HR IHC截点为< 1%，这与美国临床肿瘤学会及美国病理学家协会指南相符。临界HR染色的肿瘤的分子学类型多种多样，可能需要使用其他方法以明确其基础生物学。 The Oncologist 2015;20:474–482